2000
DOI: 10.1029/2000gl000040
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of ENA precipitation in the EUV dayglow

Abstract: Abstract.Observations

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 23 publications
2
10
0
Order By: Relevance
“…This is in good agreement with the conjecture of Stephan et al [2000] that this emission is caused by precipitating oxygen ENAs.…”
Section: May 11 2002 Stormsupporting
confidence: 81%
See 1 more Smart Citation
“…This is in good agreement with the conjecture of Stephan et al [2000] that this emission is caused by precipitating oxygen ENAs.…”
Section: May 11 2002 Stormsupporting
confidence: 81%
“…It is the general consensus of these authors that the observed enhancements are due to precipitation of energetic neutral atoms (ENA) originating in the ring current. Indeed Stephan et al [2000] has shown that various emission features exhibit a significant negative correlation with the Dst index, which is driven primarily by the strength of the ring current. Several mechanisms for this emission enhancement have been proposed, although a detailed description of the chemical and kinetic processes involved has yet to be established.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the deposited energy from the plasmasphere and the magnetosphere can be carried back to the exosphere by the upward flux of the hydrogen atoms, leading to large satellite populations and an enhanced escape rate. There is some evidence indicating a significant influence of energetic neutral particle precipitation from the ring current on the dayglow at low and mid-latitudes (<30° geomagnetic latitude)2930. Those works show that the low-latitude dayglow emissions, including the OII 83.4, OI 98.9 and 130.4 nm, as well as the H-Ly α emissions observed from the STP 78–1 satellite at 600 km altitude, are brightened during geomagnetically active times compared with quiet times.…”
Section: Resultsmentioning
confidence: 99%
“…Although we cannot quantify the above‐discussed uncertainties due to insufficient data constraints, we note that our results are consistent with previously reported observations. For example, Stephan et al [] showed a storm time brightness decrease in the dayside Ly α airglow emission as measured in the near‐zenith direction by the STP 78‐1 satellite in low Earth orbit at 600 km. In additional simulations not shown here, we successfully reproduced these observations by modeling upward viewing Ly α measurements from a 600 km vantage using our estimated quiet time and storm time H density profiles.…”
Section: Storm‐driven H Redistribution In the Terrestrial Atmospherementioning
confidence: 99%
“…Over the past few decades, it has been well established that geomagnetic storms can significantly affect the near-Earth space environment, leading to enhancement of ionospheric plasma densities [Foster and Rideout, 2005;Heelis et al, 2009;Immel and Mannucci, 2013], compression of the plasmasphere [Spasojevic et al, 2003;Huba and Krall, 2013], and heating of the thermosphere [Fuller-Rowell et al, 1994;Burns et al, 1995;Lei et al, 2010]. Variations of the atmospheric temperature, composition, and particle densities during storms can manifest as evident changes in the observations of thermospheric UV emissions [Stephan et al, 2000;Zhang et al, 2006] and exospheric H emissions [Kerr et al, 2001;Bailey and Gruntman, 2013;Kuwabara et al, 2017;Zoennchen et al, 2017].…”
Section: Introductionmentioning
confidence: 99%